Impacto socioeconómico de recolección de desechos en la calidad de vida de recicladores del botadero de basura de El Guabo - Gualpa Gudiño, Danixa María; Castillo Rojas, Mishell Estefanía (Machala: Universidad Técnica de Machala, 2023)
The following degree work was carried out in order to solve a serious problem that has been going on in a garbage dumb which is located in El Guabo city. This place has been used as a commercial sector by street vendors. This fact occurred because of mismanagement by the municipality of this city. There has not been good management and control of waste because the authorities have not designed plans, programs or projects in order to control this problematic. In addition, the local, provincial, and national authorities have been not generating many job places to benefit people who work around this place. They have not even been trying to improve their living conditions for years. Taking into account this serious problem, it was really necessary to focus on this research which was titled: Socioeconomic impact of waste collection based on the quality of life of the garbage recyclers in the garbage dump of El Guabo city. The socioeconomic impact is negative because it has been affecting the income, health, education, environment and working conditions of the recyclers. As a consequence, this activity does not allow them to improve their basic needs, so the risks are inevitable due to the exposure to waste which is highly toxic. Those people have been facing many obstacles such as lack of protection, lack of services, and illness. They only want to have access to basic services so that their families get a good life style. The sociological basis of this research is structuralism due to the fact that it is focused on the recyclers of the garbage dump of El Guabo city. They are not only independent actors who make individual decisions. They are the result of the social conditions in which they live. All these facts were evidenced taking into consideration the economic and its influence on the work environment which impacts the quality of life of the families who are living in marginality situations and as a result of this development and welfare has been stopped. In this research the methodology that was applied is called basic. It was applied because this research has been complemented with theoretical information from scientific journals. Also, some techniques and instruments such as interview, survey and observation guide. All these were used to get empirical results. On the other hand, the approach of this research was hypothetical deductive because it allowed to refute and validate the formulated hypotheses. In addition, taking into account the problems that were obtained from the diagnosis it was possible to detect that the income received were not enough and did not allow to satisfy the basic basket. Moreover, the exposure to risks and diseases are inevitable due to the little protection and safety when the recyclers carry out their economic activities which are related to recycling. The intervention proposal of this research is Awareness plan, training in protection and safety measures which are focused on recyclers in order to prevent risks and diseases. This research also has an operational plan and a schedule of activities with concrete actions that are developed to solve the current problem. In addition, it has a budget and assigned financing which allows it to be viable and feasible from the technical, economic, social and environmental dimensions.
El presente trabajo de titulación es un tema que ha adquirido la importancia de investigar debido que el botadero de basura de El Guabo se ha convertido en una fuente generadora de ingresos para gran cantidad de trabajadores informales, a su vez el origen se debe a la escasa administración del Municipio en la gestión y control de los desechos que no han diseñado planes, programas o proyectos sobre el manejo de los residuos sólidos, así mismo de las autoridades locales, provinciales, y nacionales en brindar o generar empleos para beneficiar a las personas que se dedican de dicha actividad económica y mejorar las condiciones de vida, en tal sentido, se han planteado el título “Impacto socioeconómico de recolección de desechos en la calidad de vida de recicladores del botadero de basura de El Guabo. El impacto socioeconómico es negativo dado que afecta en los ingresos, salud, educación, medio ambiente y en las condiciones laborales de los recicladores, por lo tanto, está actividad no les permite cubrir las necesidades básicas, por ende, los riesgos son inevitables debido a la exposición de los residuos y desechos que son altamente tóxicos y a las escasas medidas de prevención y protección que provocan enfermedades, siendo obstáculos y limitantes en el acceso a servicios básicos para que las familias puedan obtener una, vida digna, plena y sana. La fundamentación sociológica es el estructuralismo, dado que, la investigación se vincula con los recicladores del botadero de desechos de El Guabo, debido a que no son solo actores independientes que toman decisiones individuales, sino son el producto de las condiciones sociales en las que viven, teniendo en consideración la relación del sector económico y su influencia del ambiente laboral que repercute en la calidad de vida de las familias que viven en situaciones de marginalidad obstaculizando el desarrollo y bienestar. Por otro lado, Sociología del medio ambiente, en relación a los problemas ambientales que provoca afectaciones en la salud de los recicladores y que perjudica en el entorno natural. La metodología aplicada es de tipo básico, debido a que la investigación se ha complementado con información teórica de revistas científicas, así mismo a través de las técnicas e instrumentos como la encuesta entrevista y guía de observación ha permitido obtener resultados empíricos, , su enfoque es hipotético deductivo dado que, que refutan o validan las hipótesis formuladas, con respecto a los problemas obtenidos del diagnóstico se ha detectado que los ingresos percibidos son bajos y que no permiten satisfacer la canasta básica, así mismo la exposición a riesgos y enfermedades son inevitables, debido a las escasas medidas de protección y seguridad en realizar las actividad económicas derivadas del reciclaje. La propuesta de intervención a implementarse es Plan de sensibilización y capacitación en medidas de protección y seguridad dirigido a los recicladores para prevención de riesgos y enfermedades, a su vez cuenta con un plan operativo y un cronograma de actividades con acciones concretas que se desarrollan para la solución del problema, por otro lado, cuenta con un presupuesto y financiamiento asignado, convirtiéndose en viable y factible desde la dimensión técnica, económica, social y ambiental.
Keywords: IMPACTO SOCIOECONOMICO; DESECHO SOLIDO; RECICLADOR; CALIDAD DE VIDA